2019
DOI: 10.3847/2041-8213/ab20c8
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Lunar Transit in New Analysis of Hubble Space Telescope Observations of the Kepler-1625 System

Abstract: Observations of the Kepler-1625 system with the Kepler and Hubble Space Telescopes have suggested the presence of a candidate exomoon, Kepler-1625b I, a Neptune-radius satellite orbiting a long-period Jovian planet. Here we present a new analysis of the Hubble observations, using an independent data reduction pipeline. We find that the transit light curve is well fit with a planet-only model, with a best-fit χ 2 ν equal to 1.01. The addition of a moon does not significantly improve the fit quality. We compare … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 33 publications
2
60
0
Order By: Relevance
“…Such searches for low-amplitude photometric signals can be compromised by time-correlated systematics, whether instrumental (e.g., Kepler's sudden pixel sensitivity dropout) or astrophysical (e.g., stellar variability) in nature (Jenkins et al 2010;Christiansen et al 2013;Kipping et al 2012Kipping et al , 2015. Additionally, different detrending methodologies seem to deviate at the required 100 ppm level even for HST measurements of Kepler 1625, a star with similar brightness to the super-puffs studied here (Teachey & Kipping 2018;Kreidberg et al 2019;Teachey et al 2019;Heller et al 2019).…”
Section: Piro and Vissapragadamentioning
confidence: 80%
“…Such searches for low-amplitude photometric signals can be compromised by time-correlated systematics, whether instrumental (e.g., Kepler's sudden pixel sensitivity dropout) or astrophysical (e.g., stellar variability) in nature (Jenkins et al 2010;Christiansen et al 2013;Kipping et al 2012Kipping et al , 2015. Additionally, different detrending methodologies seem to deviate at the required 100 ppm level even for HST measurements of Kepler 1625, a star with similar brightness to the super-puffs studied here (Teachey & Kipping 2018;Kreidberg et al 2019;Teachey et al 2019;Heller et al 2019).…”
Section: Piro and Vissapragadamentioning
confidence: 80%
“…After TK18, the first E-mail: mario.sucerquia@uv.cl to investigate the combined Kepler and Hubble data into one dataset were Heller, Rodenbeck & Bruno (2019), who came up with alternative explanations for the exomoon interpretation. Also, by analysing the single Hubble transit in TK18, Kreidberg, Luger & Bedell (2019) have reported that the exomoon signal was not found. But if upcoming studies confirm it, this would be a remarkable discovery like that of the first exoplanet more than 20 years ago: 51 Pegasi b (Mayor & Queloz 1995).…”
Section: Introductionmentioning
confidence: 99%
“…6. CONCLUSIONS Given that the prospect of discovering extrasolar satellites with masses M 10 −2 M ⊕ by radial velocity, or radii R 3 × 10 −1 R ⊕ by transit techniques are bleak at present (Teachey & Kipping (2018); Kreidberg et al (2019)), we described in this work how gas signatures of Na I & K I at a hot Jupiter could be indicating the presence of a geologicallyactive satellite subject to the ambient plasma. This appears to be the case for at least one such system, WASP 49-b.…”
Section: An Exo-io At Wasp 49-b ?mentioning
confidence: 82%
“…It was shown that if the tidal Q for the planet, Q p is of the order of the equilibrium tide limit, Q p ∼ 10 12 as first derived by Goldreich & Nicholson (1977) and improved by Wu (2005a), even Earth-mass exomoons around hot Jupiters could be tidally-stable on ∼ Gyr timescales. Kepler data has not yet detected such exomoons, except for the recent tentative identification of a Uranus-sized candidate Kepler 1625-b at ∼ 1 AU (Teachey & Kipping (2018); Kreidberg et al (2019)). The observation of a close-in exomoon would in principle be able to constrain the low tidal Q values used in the literature (Barnes & O'Brien (2002); Weidner & Horne (2010)) previously set to Jupiter's ∼ 10 5 (Lainey & Tobie (2005)).…”
Section: Tidal Stability Of An Exo-iomentioning
confidence: 99%